Classification of several Yamato-75 chondrites (IV) - Miura, Yasunori; Matsumoto, Yukio (1982)
P(論文) An electron microprobe analyzer was used to determine the chemical compositions of olivines and orthopyroxenes in six chondrites, i.e. Yamato-75119,91,-75124,91,-75125,91,-75126,91,-75128,92 and -75133,93. These chondrites are classified on the basis of textural characteristics of chondrules, matrix, plagioclase and igneous glass, and on the compositions of olivines and orthopyroxenes. The statistical analyses of the experimental results show that the chondrites Yamato-75119,91,-75125,91,-75126,91 and -75128,92 are tentatively assigned to L4∿5 [i.e. L4 (67%), (67%), (83%) and (83%), respectively], and that the chondrites Yamato-75124,91 and -75133,93 are assigned to L5∿4 [i.e. L5 (67%)] and LL4∿5 [i.e. L4 (67%)], respectively. These chondrites, except the chondrites Yamato-75133,93,were possibly one single meteorite originally which was broken into many fragments during passage through the atmosphere, together with seventeen chondrites previously reported. The chondrite Yamato-75133,93 is possibly a different fragment from the above seventeen chondrites. Another sample of the chondrite Yamato-75102,74 tentatively classified as L6∿5 chondrite from different sampling area, is determined to be of L4∿5 [i.e. L4 (67%)] chondrite based on the same analytical method as the above six chondrites. The chemical compositions of plagioclases in these seven chondrites show some variation in oligoclase compositions. departmental bulletin paper